2020
DOI: 10.1097/aog.0000000000003996
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Critical Illness Among Obstetric Patients With Coronavirus Disease 2019 (COVID-19) Infection

Abstract: OBJECTIVE: To characterize symptoms and disease severity among pregnant women with coronavirus disease 2019 (COVID-19) infection, along with laboratory findings, imaging, and clinical outcomes. METHODS: Pregnant women with COVID-19 infection were identified at two affiliated hospitals in New York City from March 13 to April 19, 2020, for this case series study. Women were diagnosed with COVID-19 infection based on either universal testing on admission o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 12 publications
2
99
1
7
Order By: Relevance
“…This is consistent with other studies, which have also demonstrated that the majority of pregnant patients with COVID-19 have mild disease. 14 Known risk factors associated with severity of disease and poor outcomes with COVID-19 include medical comorbidities 15 ; however, in our cohort, patients with diabetes, hypertension, and other comorbidities were not more likely to test positive for SARS-CoV-2 infection. We may have been underpowered to investigate these differences.…”
Section: Discussionmentioning
confidence: 57%
“…This is consistent with other studies, which have also demonstrated that the majority of pregnant patients with COVID-19 have mild disease. 14 Known risk factors associated with severity of disease and poor outcomes with COVID-19 include medical comorbidities 15 ; however, in our cohort, patients with diabetes, hypertension, and other comorbidities were not more likely to test positive for SARS-CoV-2 infection. We may have been underpowered to investigate these differences.…”
Section: Discussionmentioning
confidence: 57%
“…Eight studies (95 247 women) compared pregnant populations with non-pregnant populations,2526272829303132 and four studies (2230 women) compared pregnant women with covid-19 versus pregnant women without covid-19 33343536. Forty cohort studies reported on clinical manifestations (13 018 pregnant, 85 084 non-pregnant women),25262728293031323536373839404142434445464748495051525354555657585960616263646566 45 studies reported on covid-19 related maternal outcomes (14 094 pregnant, 85 169 non-pregnant women),2526272829303132353637383940414243454647484950515354555657585961626364656667…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 22 unique cohorts of participants described in 24 studies (15 cohorts, 7 cross sectional) reported the proportion of asymptomatic infection at initial testing and/or the proportion of COVID-19 infections remaining asymptomatic throughout follow-up; study characteristics are summarized in Table 1 . Study cohorts were from the USA (n = 10) [ 6 , 9 , 60 62 , 66 , 69 , 73 , 75 , 78 , 80 , 81 ], Europe (n = 8) [ 63 , 67 , 68 , 70 , 72 , 74 , 76 , 77 ], and Asia (n = 4) [ 65 , 70 , 79 , 84 ]. Definition of asymptomatic infection was variable among studies, ranging from absence of symptoms in the previous 14 days to only absence of symptoms at time of testing.…”
Section: Resultsmentioning
confidence: 99%